City in ruins : a novel - Winslow, Don, 1953- (William Morrow, 2024)
Sometimes you have to become what you hate to protect what you love. Danny Ryan is rich. Beyond his wildest dreams rich. The former dock worker, Irish mob soldier and fugitive from the law is now a respected businessman - a Las Vegas casino mogul and billionaire silent partner in a group that owns two lavish hotels. Finally, Danny has it all: a beautiful house, a child he adores, a woman he might even fall in love with. Life is good. But then Danny reaches too far. When he tries to buy an old hotel on a prime piece of real estate with plans to build his dream resort, he triggers a war against Las Vegas power brokers, a powerful FBI agent bent on revenge and a rival casino owner with dark connections of his own. Danny thought he had buried his past, but now it reaches up to him from the grave to pull him down. Old enemies surface, and when they come for Danny they vow to take everything - not only his empire, not just his life, but all that he holds dear, including his son. To save his life and everything he loves, Danny must become the ruthless fighter he once was - and never wanted to be again. Ranging from the gritty back rooms of Providence, RI to the power corridors of Washington, DC and Wall Street to the golden casinos of Las Vegas, City in Ruins is an epic crime novel of love and hate, ambition and desperation, vengeance and compassion.